Mathematical and physical systems biology: application to pharmacokinetic drug-drug interactions and tumour growth - Cherkaoui Rbati, Mohammed (2016)
In this thesis, a multi-scale approach is provided to a pharmacokinetic and a pharmacodynamic problem.